Postexercise rehydration in man: the effects of carbohydrate content and osmolality of drinks ingested ad libitum - Evans, Gethin H; Shirreffs, Susan M; Maughan, Ronald J (Applied physiology, nutrition, and metabolism, 2009)
The effectiveness of different carbohydrate solutions in restoring fluid balance in situations of voluntary fluid intake has not been examined previously. The effect of the carbohydrate content of drinks ingested after exercise was examined in 6 males and 3 females previously dehydrated by 1.99 ± 0.07% of body mass via intermittent exercise in the heat. Beginning 30 min after the cessation of exercise, subjects drank ad libitum for a period of 120 min. Drinks contained 31 mmol·L -1 Na + as NaCl and either 0%, 2%, or 10% glucose with mean ± SD osmolalities of 74 ± 1, 188 ± 3, and 654 ± 4 mosm·kg -1 , respectively. Blood and urine samples were collected before and after exercise, midway through rehydration, and throughout a 5 h recovery period. Total fluid intake was not different among trials (0%: 2258 ± 519 mL; 2%: 2539 ± 436 mL; 10%: 2173 ± 252 mL; p = 0.173). Urine output was also not different among trials (p = 0.160). No differences among trials were observed in net fluid balance or in the fraction of the ingested drink retained. In conclusion, in situations of voluntary fluid intake, hypertonic carbohydrate-electrolyte solutions are as effective as hypotonic carbohydrate-electrolyte solutions at restoring whole-body fluid balance.